2004
DOI: 10.1302/0301-620x.86b6.14426
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with traction on the hip during arthroscopy

Abstract: We studied 16 hips (eight cadaver specimens) using arthrography, arthroscopy and anatomical dissection, under incremental traction of up to a maximum of 64 kg, to determine the relationship of the portals to nearby neurovascular structures. The distance of each arthroscopic portal (anterior, anterolateral, and posterolateral) to the associated neurovascular structures was measured after the application of 23 kg of traction. Traction of up to 64 kg on the lower limb failed to produce evidence of labral or capsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Due to its close proximity to the AP's insertion point, the LFCN is considered to be the structure most at risk during SHA 19 . Previous smaller cadaveric studies have found the nerve to lie 3-15mm from the AP insertion point on average, with considerable variation in the path of the nerve relative to the AP [22][23][24] . Similarly, a study by Wastson et al examined the path of the LFCN in one hundred MRI scans and found the mean distance of the LFCN from the AP insertion point to be 6.37mm (though this study did not account for portal diameter in its measurements) 28 .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Due to its close proximity to the AP's insertion point, the LFCN is considered to be the structure most at risk during SHA 19 . Previous smaller cadaveric studies have found the nerve to lie 3-15mm from the AP insertion point on average, with considerable variation in the path of the nerve relative to the AP [22][23][24] . Similarly, a study by Wastson et al examined the path of the LFCN in one hundred MRI scans and found the mean distance of the LFCN from the AP insertion point to be 6.37mm (though this study did not account for portal diameter in its measurements) 28 .…”
Section: Discussionmentioning
confidence: 88%
“…Although previous cadaveric studies into the risk during AP placement have emphasized the close proximity of the LFCN to the AP, these studies are few in number and small in size 19,[22][23][24] . Previous cadaveric studies into this risk during the MIAA have focused on the path of this nerve in relation to bony landmarks, not the nerve's proximity to the incision at its lateralized site 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Complications of hip arthroscopy reported in the literature include neurapraxia, iatrogenic chondral damage, femoral neck fracture, fluid extravasation, and heterotopic ossification. 12,13) In our patients, there were no such complications except transient compression neuropathy of the perineal nerve. In addition, arthroscopic osteochondroplasty at the head-neck junction did not cause physeal growth disturbance even though patients were skeletally immature at the time of hip arthroscopy and the youngest patient in our series was 12.2 years old.…”
Section: Discussionmentioning
confidence: 41%
“…The association between these major vascular structures and the standard hip arthroscopy portals was evaluated by Elsaidi et al [7], who reported the posterolateral portal was located a mean distance of 19 mm from the ascending branch of the lateral femoral circumflex artery. Even with the addition of traction up to 23 kg, there was no change in the distance from the portal sites to their associated neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%